Hubungan Antara Pelatihan, Kepuasan Kerja dan Kinerja Tempat Kerja pada Organisasi Pelayanan Publik Studi pada Satuan Polisi Pamong Praja dan Pemadam Kebakaran Kabupaten Semarang - Arisadewi, Firdania Rarastiti (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2020)
Human resources in an organization is an important and influential aspect in the organization's activities and productivity. Good human resources will produce good employee performance which will then have an impact on producing good workplace performance. The purpose of this study was to determine whether training and job satisfaction affect workplace performance at the Civil Service Police Unit and Semarang Fire Department. The sampling technique in this study used simple random sampling, where 126 people were taken from the entire population. The research method uses multiple linear regression analysis, t test, F test and path analysis. The results showed that training had no positive and significant effect on job satisfaction, training had no positive and significant effect on workplace performance and job satisfaction had a positive and significant effect on workplace performance. With the path analtsis it is known that the job satisfaction variable does not meet the requirements to be an interverning variable.